The Impact of Endometrioma Treatment on Ovarian Reserve (Central Asian Journal of Medical Sciences, 2020)
Objectives: To evaluate the ovarian reserve by measuring AMH level after the both treatment of drug and surgery for Endometrioma. Methods: We studied 129 patients who have diagnosed with ovarian endometrioma, aged 20-46 years, using case-control study design. There are 4 groups with medication and surgeries. Results: There were significant reduction of pain in patients who received synthetic progestin (p = 0.001) groups. Serum AMH were 3.48 ± 0.9 before treatment and 3.41 ± 1.0 after treatment respectively (p = 0.456). Prior treatment of laparoscopic surgery with progestin 3 months, it decreases abdominal lower pain (p = 0.001) and dysmenorrhea (p = 0.001). Serum AMH level were 3.11 ± 1.8 before surgery and 2.21 ± 0.2 after surgery, respectively (p = 0.005). Conclusions: Laparoscopic surgery might be decrease ovarian reserve which leads to infertility later life in women who has ovarian endometrioma with ovarian cystectomy.